Implementasi Undang-Undang Perlindungan Konsumen dalam Industri Perbankan Syariah - Irfan Ridha; Ahmad Kalingga; Aisyah Putri Indra; Alfajar Ahmad Abujibril; Alisha Zahra Saadiya; Anisa Ayu Putri; Annisa Mardiya Hakim; Arinaldi Arinaldi; Arina Putri Agustina; Ayu Saputri; Bintang Reynaldo Putra (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
The Consumer Protection Law (UU 22/2020) has provided a legal basis for consumer protection in the banking industry. The implementation of this law is important in the Islamic banking industry due to its consistency with sharia values which place justice and balance as the main principles. The purpose of this study is to analyze the implementation of the Consumer Protection Act in the Islamic banking industry and evaluate the effectiveness of its implementation. This research uses a qualitative approach with a literature study. Data was collected through analysis of book literature and analysis of documents related to the implementation of the Consumer Protection Act. The results of the study show how actual implementation of the Consumer Protection Law is in its operational procedures. However, there are several challenges in implementation, such as the lack of awareness and understanding of customers about their rights, as well as a lack of adequate human resources and information technology to meet the requirements of the law. This study recommends that Islamic banks increase consumer empowerment campaigns and invest in adequate human resources and information technology to increase the effectiveness of the implementation of the Consumer Protection Act. This is expected to increase customer confidence in the sharia banking industry and support sustainable industry growth.